Metacognitive strategy training on pre-university students’ listening achievement and metacognitive awareness - Saratha, K. Krishnan (2021)
Even though listening skill in English is commonly tested, metacognitive strategy is seldom taught to students. This study examined the effectiveness of metacognitive strategy training (MST) on students’ MUET listening test; on students’ metacognitive awareness based on planning-evaluation, directed attention, personal knowledge, mental translation and problem solving; students’ use of metacognitive strategies over the treatment period and their perceptions on MST in L2 listening. 62 pre-university students from one of the matriculation colleges participated in this study which adopted a mixed-method design. Quantitative data using the quasi-experimental design were elicited to measure students’ listening achievement while metacognitive awareness was assessed using the Metacognitive Awareness Listening Questionnaire (MALQ). Subsequently, qualitative data were obtained through reflective journals and focus group interviews. ANCOVA revealed that MST had immediate and delayed effects on the treatment groups’ listening achievement and metacognitive awareness. The MALQ survey displayed that MST had immediate effect on students’ planning-evaluation, directed-attention strategy, and problem-solving strategies while the post- delayed findings found there were effects on directed attention strategy. Qualitative findings revealed that students utilized planning-evaluation, directed-attention and problem-solving strategies and they perceived MST as effective and helpful in improving listening scores and metacognitive awareness. This study contributes to the body of knowledge on metacognitive strategies in L2 listening and the MST module could be used by educators to integrate MST in teaching listening.